TOTAL PHENOLIC, FLAVONOID, TANNIN CONTENTS, AND ANTIOXIDANT ACTIVITY OF ORGANIC EXTRACTS OF VEGETATIVE AND FLOWERING STAGES OF MECARDONIA PROCUMBENS (MILL.) SWALL. - CHAITRA B NEGLUR; ASHWINI M GAJAKOSH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study is to assess the total amount of phenols, flavonoid, and tannin content along with its antioxidant property of two physiological different stages such as vegetative and flowering in Mecardonia procumbens (Mill.) Swall. Methods: subsequent extraction s done by socklet apparatus with solvents of increasing polarity: hexane, acetone, methanol, and to estimated for the biological metabolites. Results: Stage of the plant significantly affected the quality of the phenols, flavonoids, and tannins. The highest amount of phenol (86.25±1.03 Gallic acid equivalents per gram of dry weight [GAE/g DW]) was reported in acetone extract in flowering sage similar result was with the flavanoid W(14.25±0.52 GAE/g DW). Whereas tannins were high in methanol extract of the flowering stage (49.52±1.02 mg catechin/g DW). The best scavenging activity was found in the flowering stage of acetone extract (3.5±0.06 μg/mL) and total antioxidant property was also in flowering stage of methanol extract (97.48 mg GAE/g DW) the M. procumbens. Conclusion: Extracts of acetone and methanol were more effective and could be used as preservatives in food or pharmaceuticals.